Food insecurity and food consumption by season in households with children in an Arctic city: a cross-sectional study - Catherine Huet; James D. Ford; Victoria L. Edge; Jamal Shirley; Nia King; IHACC Research Team; Sherilee L. Harper (BMC, 2017)
Abstract Background High rates of food insecurity are documented among Inuit households in Canada; however, data on food insecurity prevalence and seasonality for Inuit households with children are lacking, especially in city centres. This project: (1) compared food consumption patterns for households with and without children, (2) compared the prevalence of food insecurity for households with and without children, (3) compared food consumption patterns and food insecurity prevalence between seasons, and (4) identified factors associated with food insecurity in households with children in Iqaluit, Nunavut, Canada. Methods Randomly selected households were surveyed in Iqaluit in September 2012 and May 2013. Household food security status was determined using an adapted United States Department of Agriculture Household Food Security Survey Module. Univariable logistic regressions were used to examine unconditional associations between food security status and demographics, socioeconomics, frequency of food consumption, and method of food preparation in households with children by season. Results Households with children (n = 431) and without children (n = 468) participated in the survey. Food insecurity was identified in 32.9% (95% CI: 28.5-37.4%) of households with children; this was significantly higher than in households without children (23.2%, 95% CI: 19.4-27.1%). The prevalence of household food insecurity did not significantly differ by season. Demographic and socioeconomic characteristics of the person responsible for food preparation, including low formal education attainment (ORSept = 4.3, 95% CI: 2.3-8.0; ORMay = 3.2, 95% CI: 1.8-5.8), unemployment (ORSept = 1.1, 95% CI: 1.1-1.3; ORMay = 1.3, 95% CI: 1.1-1.5), and Inuit identity (ORSept = 8.9, 95% CI: 3.4-23.5; ORMay = 21.8, 95% CI: 6.6-72.4), were associated with increased odds of food insecurity in households with children. Fruit and vegetable consumption (ORSept = 0.4, 95% CI: 0.2-0.8; ORMay = 0.5, 95% CI: 0.2-0.9), as well as eating cooked (ORSept = 0.5, 95% CI: 0.3-1.0; ORMay = 0.5, 95% CI: 0.3-0.9) and raw (ORSept = 1.7, 95% CI: 0.9-3.0; ORMay = 1.8, 95% CI: 1.0-3.1) fish were associated with decreased odds of food insecurity among households with children, while eating frozen meat and/or fish (ORSept = 2.6, 95% CI: 1.4-5.0; ORMay = 2.0, 95% CI: 1.1-3.7) was associated with increased odds of food insecurity. Conclusions Food insecurity is high among households with children in Iqaluit. Despite the partial subsistence livelihoods of many Inuit in the city, we found no seasonal differences in food security and food consumption for households with children. Interventions aiming to decrease food insecurity in these households should consider food consumption habits, and the reported demographic and socioeconomic determinants of food insecurity.